Anxieties Disorder and Deviant Behaviors among Secondary School Studies in Obubra Local Government Area of Cross River State - A., Okpechi, Philip; U., Ekpang Pauline (International Journal of Educational Technology and Learning, 2018)
This study was to determine the relationship between anxiety disorder and deviant behavior among senior secondary school students in Obubra Local Government Area of Cross River State. Various deviant behaviours of varying degrees ranging from truancy, lateness, fighting, bullying, cheating in examination, vandalism, drugs abuse, rape, disrespect to authority etc. leading to inadequate preparation towards academic test and examinations. Based on the above, hypothesis was formulated to guide the study. The study was delimited to Obubra Local Government Area and SS two students were used for the study. Anxiety disorder was delimited to phobic anxiety disorder. The instrument use was the Anxiety Disorder and Deviant Behavior Questionnaire (ADDBP) and it contained forty 40 items. A sample population of 247 students distributed among the five secondary schools in Obubra Local Government Area of Cross River State – Nigeria were used for the survey. Pearson product correlation coefficient was used to analyze the data. Based on the research findings recommendations were made.